Genetic parameters of Eucalyptus pilularis resistance to rust in controlled and field conditions - Baroni, Gabriel de Resende; de Pieri, Cristiane [UNESP]; Furtado, Edson Luiz [UNESP]; da Silva, Paulo Henrique Muller (Springer Nature, 2020)
This study compared the susceptibility of E. pilularis progenies (from Brazilian populations) to myrtle rust under controlled and field conditions in Brazil. High levels of resistance were observed under both controlled (96% resistant individuals) and field (97% resistant individuals) conditions, despite the optimum climatic conditions for disease development. Assessment of field susceptibility was more accurate at 14 months compared to 2–6 months. Individual heritability was higher under controlled conditions (h2 a = 0.81) compared to field conditions (h2 a = 0.17), indicating the former to be a more reliable method for testing susceptibility. Eucalyptus pilularis is rust tolerant while heritability is higher under controlled conditions compared to field conditions.
Keywords: Austropuccinia psidii; Heritability; Myrtle rust; Progeny trial